1985
DOI: 10.1139/b85-182
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and flavonoid chemical confirmation of intergeneric hybridization between Tolmiea and Tellima (Saxifragaceae)

Abstract: SOLTIS, D. E., and B. A. BOHM. 1985. Chromosomal and flavonoid chemical confirmation of intergeneric hybridization between Tolmiea and Tellima (Saxifragaceae). Can. J. Bot. 63: 1309-13 12. Two putative intergeneric hybrids between Tolrniea menziesii and Tellima grandi'ora were discovered in Oregon and Washington. These plants are morphologically intermediate in several floral features between the presumed parental taxa. Evidence from flavonoid chemistry and karyology support the contention that these plants ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Clearly, several clades found in the strict consensus of cpDNA and ITS sequence trees represent strongly supported relationships: (1) Tolmiea 2x and 4x; (2) M. ovalis and M. breweri; and (3) L. parviflorum and L. affine. These sister groups all are in agreement with long-standing views based on morphology and in some cases chemical data (e.g., Soltis and Bohm 1985;Rosendahl 1914;Small and Rydberg 1905).…”
Section: Systematic Implications For the Heuchera Groupsupporting
confidence: 88%
See 2 more Smart Citations
“…Clearly, several clades found in the strict consensus of cpDNA and ITS sequence trees represent strongly supported relationships: (1) Tolmiea 2x and 4x; (2) M. ovalis and M. breweri; and (3) L. parviflorum and L. affine. These sister groups all are in agreement with long-standing views based on morphology and in some cases chemical data (e.g., Soltis and Bohm 1985;Rosendahl 1914;Small and Rydberg 1905).…”
Section: Systematic Implications For the Heuchera Groupsupporting
confidence: 88%
“…Second, the occurrence of chloroplast capture agrees with the basic biology of the Heuchera group. Genera such as Heuchera are well known for frequent interspecific hybridization (Rosendahl et al 1936), and intergeneric hybrids have been reported between Tolmiea and Tellima (Soltis and Bohm 1985), Mitella and Conimitella (Soltis and Soltis 1986), Heuchera and Mitella, and Heuchera and Tiarella (reviewed in Spongberg 1972). Although such intergeneric hybrids are rare, they nonetheless illustrate the potential for hybridization and chloroplast capture to occur on a broad scale throughout the group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the remaining four monotypic genera (Bensoniella, Conimitella, Elmera, and Tellima) are solely distributed in western North America. Six of these genera are known to hybridize (Soltis and Bohm, 1985;Soltis and Soltis, 1986;Soltis et al, 1991), with intergeneric hybrids being reported between Heuchera and Tiarella (Spongberg, 1972), Tellima and Tolmiea (Soltis and Bohm, 1985), and Mitella and Conimitella (Soltis and Soltis, 1986). Numerous interspecific hybrids have been reported within Heuchera (Rosendahl et al, 1936).…”
Section: Introductionmentioning
confidence: 99%
“…Gray, Mitella L., and Heuchera L.). This included intergeneric hybridization between Heuchera and Tiarella , Tellima and Tolmiea , Mitella and Conimitella , and interspecific hybridization in Heuchera (e.g., Rosendahl et al, 1936; Spongberg, 1972; Soltis & Bohm, 1985; Soltis & Soltis, 1986). No hybridization events have been reported in Mukdenia species, but we cannot rule it out here.…”
Section: Discussionmentioning
confidence: 99%